Analysis of Marketing Strategy of Livehouse Bars - Li, Zhenran (Transactions on Economics, Business and Management Research, 2024)
With the popularity of music culture around the world, Livehouse bars have gained wide attention and are rapidly developing in domestic and foreign markets. By analyzing the target market positioning, SWOT analysis, and marketing strategy of Chinese Livehouse bars, this paper puts forward the existing problems and causes in the experience marketing of Chinese Livehouse bars and puts forward optimization suggestions.